Counselling in the Northern Native - Darou, Wes G. (Canadian Journal of Counselling and Psychotherapy, 2011)
It would appear that recurrent problems exist between counsellor and Native clients. This paper attempts to delineate these problems and suggests certain directions to counsellors. Several attitude or value differences, often unrecognized, seem to exist between Natives and Non-Natives. Empirical studies show that Native counsellors are preferred and are given more important material, non-directive approaches are disliked, and the concept of career choice may not hold in northern communities. In conclusion it is suggested that counsellors need to show flexibility and understanding of inter-ethnic issues.